PERKEMBANGAN INDUSTRI PERBANKAN DI ERA DIGITAL - Annisa Indah Mutiasari (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2020)
The Industrial Revolution 4.0 is an opportunity for the banking industry in Indonesia to be more innovative in providing excellent service to all customers. Service innovation in the use of information technology encourages banks to enter the era of digital banking services. The purpose of this study is to determine the development of digital banking industry services in Indonesia. The rapid development of digital banking technology is a new challenge for the banking world. The banking industry as a service industry that is developing and capable of driving Indonesia's economic growth is faced with two choices, namely adopting digital technology so that banks can survive or remain conventional, but slowly die.